The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/electronics11010022
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Operation of Integrated Energy Microgrid with Energy Storage Based on Short-Term Load Forecasting

Abstract: This research proposes an optimization technique for an integrated energy system that includes an accurate prediction model and various energy storage forms to increase load forecast accuracy and coordinated control of various energies in the current integrated energy system. An artificial neural network is utilized to create an accurate short-term load forecasting model to effectively predict user demand. The 0–1 mixed integer linear programming approach is used to analyze the optimal control strategy for mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Furthermore, the study concluded that microgrids are experiencing growing global interest and can derive advantages from the effective implementation of converter control techniques, energy management systems, power quality enhancement strategies, and the optimal integration of electric vehicles and energy storage systems. Additionally, a day-ahead optimal scheduling approach for integrated energy systems was introduced, which incorporates precise load prediction models and multiple energy storage technologies to enhance economic optimization [27]. The integrated energy system was represented by a mixed-integer linear programming (MILP) model, where the goal function aimed at optimizing comprehensive income.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the study concluded that microgrids are experiencing growing global interest and can derive advantages from the effective implementation of converter control techniques, energy management systems, power quality enhancement strategies, and the optimal integration of electric vehicles and energy storage systems. Additionally, a day-ahead optimal scheduling approach for integrated energy systems was introduced, which incorporates precise load prediction models and multiple energy storage technologies to enhance economic optimization [27]. The integrated energy system was represented by a mixed-integer linear programming (MILP) model, where the goal function aimed at optimizing comprehensive income.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fossil fuels are facing the problems of depletion and environmental pollution, and to alleviate this problem, the integrated energy system (IES) can improve the utilization of energy by unified planning, design, and operation optimization of multiple energy sources such as electricity, gas, and heat [1][2][3]. Therefore, IESs have been rapidly developed in various countries and regions in recent years and are one of the popular research areas at the intersection of electrical engineering, energy, thermal, and low carbon economy [4][5][6][7]. However, due to the integration of multiple energy systems in the IES, disturbances in one subsystem have the potential to be transmitted to other subsystems via the coupling elements, thereby resulting in an impact on this system.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [21] adopt the multicycle prediction method of renewable energy generation and load based on automatic reinforcement learning and propose an optimal dispatching model of the isolated microgrid. Dong H et al [22] propose an integrated energy system optimization technique, including accurate prediction models and multiple forms of energy storage, to improve the load forecasting accuracy and coordinated control of various energy sources in the current integrated energy system. In addition, demand response is also an important factor to be considered in the operation of the microgrid.…”
Section: Introductionmentioning
confidence: 99%